Hypothermia Induced Impairment of Platelets: Assessment With Multiplate vs. ROTEM—An In Vitro Study - Wallner, Bernd; Schenk, Bettina; Paal, Peter; Falk, Markus; Strapazzon, Giacomo; Martini, Wenjun Z.; Brugger, Hermann; Fries, Dietmar (Frontiers in Physiology, 2022)
Abstract Introduction: This experimental in vitro study aimed to identify and characterize hypothermia-associated coagulopathy and to compare changes in mild to severe hypothermia with the quantitative measurement of rotational thromboelastometry (ROTEM) and multiple-electrode aggregometry (MULTIPLATE). Methods: Whole blood samples from 18 healthy volunteers were analyzed at the target temperatures of 37°C, 32°C, 24°C, 18°C, and 13.7°C with ROTEM (ExTEM, InTEM and FibTEM) and MULTIPLATE using the arachidonic acid 0.5 mM (ASPI), thrombin receptor-activating peptide-6 32 µM (TRAP) and adenosine diphosphate 6.4 µM (ADP) tests at the corresponding incubating temperatures for coagulation assessment. Results: Compared to baseline (37°C) values ROTEM measurements of clotting time (CT) was prolonged by 98% (at 18°C), clot formation time (CFT) was prolonged by 205% and the alpha angle dropped to 76% at 13.7°C (p<0.001). At 24.0°C CT was prolonged by 56% and CFT by 53%. Maximum clot firmness was only slightly reduced by ≤2% at 13.7°C. Platelet function measured by MULTIPLATE was reduced with decreasing temperature (p<0.001): AUC at 13.7°C -96% (ADP), -92% (ASPI) and -91% (TRAP). Conclusion: Hypothermia impairs coagulation by prolonging coagulation clotting time and by decreasing the velocity of clot formation in ROTEM measurements. MULTIPLATE testing confirms a linear decrease in platelet function with decreasing temperatures, but ROTEM fails to adequately detect hypothermia induced impairment of platelet function.